1979
DOI: 10.1002/hlca.19790620410
|View full text |Cite
|
Sign up to set email alerts
|

Durch elektrisch geladene Ionophore induzierter Ionentransport in Modellmembranen mit Selektivität für Magnesium und Calcium

Abstract: SummaryDifferent lipophilic P-diketones have been prepared. Some preferably transport Mg2+ and Ca2+ through PVC-based liquid membranes when a pH-gradient is applied across the membrane. A theoretical model is presented that allows a description of potentiometrically determined ion selectivities as well as transport selectivities obtained under zero current and electrodialytic conditions, respectively. The expectations based on this model are in agreement with the experimental evidence presented. Some membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

1979
1979
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…9 After Simon 10 published information about tridodecylamine ionophore for hydrogen sensing, we synthesized various types of tertiary amine compound ionophores, and strived to understand the response characteristics of these ionophores. [11][12][13][14][15] Particularly, after our result concerning SCE based on the tribenzylamine (TBA) ionophore 16 was published, which had a wider response range than the electrodes with tridodecylamine (TDDA) ionophore, many types of aromatic tertiary amine compound ionophores were synthesized and studied. [17][18][19][20][21] We found that the response ranges shifted to an alkali range (toward pH 14) by extending the chain length between the phenyl ring and nitrogen in the ionophores, and were able to synthesize ionophores that exhibited a linear response up to pH 14.…”
Section: Introductionmentioning
confidence: 99%
“…9 After Simon 10 published information about tridodecylamine ionophore for hydrogen sensing, we synthesized various types of tertiary amine compound ionophores, and strived to understand the response characteristics of these ionophores. [11][12][13][14][15] Particularly, after our result concerning SCE based on the tribenzylamine (TBA) ionophore 16 was published, which had a wider response range than the electrodes with tridodecylamine (TDDA) ionophore, many types of aromatic tertiary amine compound ionophores were synthesized and studied. [17][18][19][20][21] We found that the response ranges shifted to an alkali range (toward pH 14) by extending the chain length between the phenyl ring and nitrogen in the ionophores, and were able to synthesize ionophores that exhibited a linear response up to pH 14.…”
Section: Introductionmentioning
confidence: 99%
“…2 Simon et al developed different PVC membrane pH electrodes based upon tri-n-dodecylamine, which gave good response characteristics. [3][4][5][6][7][8] Wu and Yu prepared a pH-sensitive electrode using methyldioctadecylamine (MDODA) as a neutral carrier.9 Later, some authors continued similar research, and other compounds have been investigated as ionophores for hydrogen ions, many of which can be used for a very wide range of pH values. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Calixarenes are metacylclophanes comprising phenolic and methylene units.…”
mentioning
confidence: 99%
“…7 predicts transport up to diffusion equilibrium where it finally holds that However, this equilibration transport proceeds with the maximum rate only as long as (8) …”
Section: )mentioning
confidence: 98%
“…5 and 6 apply, is the mediated transport of ions of a given charge z (cations or anions) across membranes that contain electrically charged carriers 171 [8] or combinations of charged and neutral carriers [9]. In this case, the presence of at least two permeating substrates N, namely the ions I' and J', is required for inducing a transport at zero current.…”
Section: )mentioning
confidence: 99%